Acceptability of a COVID-19 vaccine and role of knowledge, attitudes and beliefs on vaccination willingness among medical students - Kaya, Mehmet Onur; Yakar, Burkay; Pamukcu, Esra; Önalan, Erhan; Akkoc, Ramazan Fazıl; Pirincci, Edibe; Gursu, M.ferit (My University, 2021)
Objectives: Vaccination to the population is the most effective way to get rid of the COVID-19 pandemic, which currently has no effective treatment. For the high vaccine acceptance rate, it is important to determine the vaccine willingness of individuals and the barriers to vaccination. We aimed to determine the acceptability of the COVID-19 vaccine and the effect of attitudes, perception and beliefs on vaccination willingness among medical students. Methods: In February 2020, a cross-sectional survey was conducted online among medical student. A total of 734 medical students out of 980 medical students answered the questionnaire forms (response rate: 75.4%). The online questionnaire collected socio-demographic characteristics, attitudes, risk perception and beliefs about the COVID-19 pandemic and vaccine. Vaccine hesitancy, rejection and acceptance were determined by self-report of medical students. Results: Total of 739 medical students included study. Students declared that 60.1% (n = 444) of them to be willing to vaccinated, 14.2% (n = 105) refused and 25.7% (n = 190) were not sure. Covid-19 willingness to be vaccinated was higher in female (p = 0.005), clinical students (p < 0.001), those who ever tested for COVID- 19 (p = 0.002), those who had covid-19 infection history in the family (p = 0.043), those who had COVID-19 and COVID-19 vaccine education (p = 0.001). Positive attitudes skor and higher knowledge scores were related with highly willingness to be vaccinated. High beliefs score (positive beliefs) was found to be associated with a higher willingness to be vaccinated (p < 0.001). Conclusions: Although the majority of the study population willingness to be vaccinated, one-third of medical students are hesitant about vaccination. Education, positive attitude and beliefs are related to higher willingness to vaccination.The COVID-19 pandemic immunization programs should be designed to remove barriers to negative vaccine beliefs and perception.
Keywords: Eğitim; Eğitim Araştırmaları; Halk ve Çevre Sağlığı; Sağlık Politikaları ve Hizmetleri; Psikoloji